New Frontiers in Enterprise Risk Management - Olson, David L.; Olson, David L.; Wu, Desheng.; Wu, Desheng. (Springer Berlin Heidelberg : Imprint: Springer, 2008)
This book provides introductory material about enterprise risk management, and the role of risk in decision making. It presents enterprise risk management from perspectives of finance, accounting, insurance, supply chain operations, and project management. Technology tools are addressed, to include financial models of risk as well as accounting aspects using data envelopment analysis, neural network tools for credit risk evaluation, and real option analysis applied to information technology outsourcing. Three chapters present enterprise risk management experience in China, to include banking, chemical plant operations, and information technology. .